Pengaruh Return On Invesment, Earning Per Share dan Devidend Per Share Terhadap Harga Saham Sektor Manufaktur Yang Ada Di BEI Tahun 2019-2021 - I Wayan Danaswara; Baiq Kisnawati; Herawati Khotmi (Akuntabel: Jurnal Ilmiah Akuntansi, 2025)
In 2019-2021, the composite stock price index experienced uneasy fluctuations which resulted in fluctuations in the joint stock price. This study was conducted with the aim of knowing the effect of Return On Investment (ROI), Earning Per Share (EPS) and Dividend Per Share (DPS) on stock prices of companies engaged in the manufacturing sector from 2019 to 2021. This study uses secondary data sources. sourced directly from the company's official website and the official website of the Indonesian Stock Exchange, where the data collection method used is the documentation method directly from the official website source. The data analysis technique used in this research is quantitative descriptive analysis. Based on the results of this study conducted in manufacturing sector companies from 2019 to 2021, it shows that Return On Investment (ROI) has no effect on stockprices in the manufacturing sector while Earning Per Share (EPS) and Dividend Per Share (DPS) have an influence on stock prices of the manufacturing sector on the IDX in 2019-2021.